EFEKTIFITAS LATIHAN JALAN KAKI TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE 2 DI PUSKESMAS LANGSA KOTA - Alfian Helmi; Nora Hayani; Eva Sulistiany; Elfida Elfida; Zulkarnaini Zulkarnaini; Azwarni Azwarni; Lina Lina (LPSDI Bina Patria, 2023)
Physical exercise is the initial effort to prevent, control, and overcome diabetes. explains that physical exercise causes an increase in blood pressure, more capillary nets are opened so that more insulin receptors are available and receptors become more active which will affect the decrease in glucose in diabetic patients. Diabetics who do walking exercise at least 2 hours / week, compared with inactive individuals, have a mortality rate of 30% lower and the death rate due to cardiovascular disease (CVD) is 34% lower. Based on the results of several expert studies and preliminary observations conducted by researchers at the Langsa Kota Health Center, Type 2 Diabetes Mellitus was found to be a disease that ranks in the top three of the 20 most diseases. This study aims to determine the effectiveness of road training to decrease blood sugar levels in Type 2 Diabetes Mellitus patients in Langsa Kota Health Center. The results of the study showed that there was a difference in the mean value of blood sugar levels between before and after walking exercise, namely the mean value of blood sugar levels before walking exercise was 359.67, while the mean value of blood sugar levels after walking exercise was 265.13 based on the results of the T-test statistical analysis. The dependent test obtained a p-value of 0.000 (<0.05), this shows that there is an effect of walking exercise on reducing blood sugar levels in patients with type 2 diabetes mellitus at the Langsa City Health Center The researcher suggested that health institutions develop and implement the quality of nursing services for patients with diabetes mellitus by conducting road exercise interventions